Penerapan Empty Chair Therapy pada Individu Dewasa dengan Diagnosa Episode Depresif Ringan - Erika Prima Yola; Pranungsari, Dessy (Psyche 165 Journal, 2023)
Depression has a serious impact that includes emotional, motivational, behavioral, physical and cognitive domains. One of the vulnerability factors for depression is the presence of stressful life events. According to the Humanistic view, a person can experience depression when they cannot fill their existence with meaning. Gestalt counseling is a counseling method that is often used in the humanistic approach because it has the main goal of achieving awareness centered on "here" and "now". One of the intervention methods in gestalt counseling is the empty chair technique. In this technique two chairs are placed in the middle of the room and the client sits while playing the role of top dog and under dog alternately. The subject in this study was a 44-year-old woman who experienced mild depressive episode disorder.  Data collection methods used are observation, interviews and psychological tests consisting of cognitive tests (WAIS), personality (Graphic), SSCT (Sack's Sentence Completion Test) and Back Depression Inventory (BDI). This research uses a quantitative approach with an experimental method using a single case pre test and post test design. Researchers used the empty chair technique to reduce depression in the subject. The intervention results show that the empty chair technique can be used as an intervention for patients with mild depressive episode disorder. This is evidenced by a positive change related to depressive symptoms in the subject. Meanwhile, based on the calculation of the BDI score, there was a decrease in the score from the original pre-test of 40 (severe depressive) down to 19 (Mild) in the post-test.